Video Teaser Batik Edu-Tourism Sebagai Promosi Iconic Pariwisata Kota Pekalongan - Wenti Ayu Sunarjo; Victorianus Aries Siswanto; Amalia Ilmiani (JURNAL LITBANG KOTA PEKALONGAN, 2021)
This research produces information products about Pekalongan city batik educational tourism packaged in audio-visual form with the aim of increasing Pekalongan City's daytime power through audio-visual promotional media innovations that carry the concept of educational travel on the local wisdom product "Batik" which is the identity of Pekalongan City, which can attract tourists to visit Pekalongan city to take an educational tour after watching Video Teaser Batik Edu-Tourism. Research and development research or research and development (R&D) with a qualitative approach that produces competitive video innovations in promoting batik educational tourism. Batik educational tourism locations are presented based on five useful concepts of batik edu-tourism, namely: learning tourism, technique tourism, heritage tourism, community tourism, and shopping tourism which are also the hallmark or differentiation of the edu-tourism video in this video. The selection of destinations in the video is due to the prominent potential in tourism and batik education and refers to the prima donna destinations in Pekalongan City. In line with the branding of the city of Pekalongan, namely the world city of batik, this video is a special attraction for tourists who watch, as evidenced by the enthusiasm of the batik-edu tourism teaser video viewers which has increased significantly. Keywords: Batik, edu-tourism, video teaser, iconic, Pekalongan